Stopping Macroplastic and Microplastic Pollution at Source by Installing Novel Technologies in River Estuaries and Waste Water Treatment Plants: The CLAIM Project - Gkanasos, Athanasios; Tsiaras, Kostas; Triantaphyllidis, George; Panagopoulos, Aleksandros; Pantazakos, George; Owens, Tristan; Karametsis, Christos; Pollani, Annika; Nikoli, Elisabeth; Katsafados, Nikolaos; Triantafyllou, George (Frontiers in Marine Science, 2021)
Marine pollution from debris is a major issue nowadays, since every year large amounts of litter enter into the sea. Under the Horizon 2020 framework and within the Cleaning Litter by developing and Applying Innovative Methods in European Seas (CLAIM) project, innovative devices were designed, developed, tested and applied in laboratory and in the field. These consisted of a system named CLEAN TRASH for the prevention of macrolitter in river estuaries before entering the Sea and a filtering system for microplastics (MPs), to be placed at waste water treatment plants (WWTP). Laboratory experiments showed that macrolitters were blocked by 90% by the CLEAN TRASH system, while during the sea testing period at the Kifissos river estuary, a significant source of terrestrial based litter for the Saronikos Gulf, a total amount of 1,175 kg of litter was collected in 38 days before entering the sea, of which the 708 kg (60%) were plastic debris of various sizes and another 164 kg (14%) of styrofoam parts. The lab scale prototype of the filtering system for MPs had an efficiency of about 95%. The upscaled device was tested at the Megara WWTP and was able to withhold a significant amount of MPs. The theoretical contribution of such devices toward the reduction of plastic pollution in the Saronikos Gulf area and the Natura conservation areas therein, was also studied with the use of a 3-D coupled Hydrodynamic-Lagrangian litter tracking model. In all experiments performed, the installation of the above devices for a period of 2 years, resulted in a microplastics reduction by about 87% and a macroplastics reduction ranging from 13 to 43%, depending on the sources.